Deeping Our Relationships for Healing: Our Land, Our People, Our Freedom (Mary Ann Liebert, 2023)
The relationship with Indigenous people and the United States is devastating and complex. There is shame carried within this relationship. The shame holds the power to force society, systems, and individuals to create new narratives. Narratives that both ignore the brutal past and devalue the gifts of the people forcibly violated. Thus, creating a society that hides its past and embeds privilege and value for some, while dehumanizing and making others invisible. For Indigenous people, this invisibility has deep impact, one of which is generational health disparities. Indigenous people are highly visible in statistics of despair, such as violence against women, murder, infant mortality, neonatal abstinence syndrome, and more. The health statistics for Indigenous people are often not coupled with the stories of why such despair exists. The stories of shame have been erased from our textbooks but not our bodies, a new narrative created, resulting in irreparable harm to Indigenous people. This harm, however, is not isolated to Indigenous people, the harm is shared with all people. The absence of indigenous ways of being, knowing, and connecting has immense impact on our nation's ability to live in relationship with this land and with each other. There is great divisiveness in our world and country today. This divisiveness can be easily seen with a quick social media scroll or a click on the television. This divide does not serve us well as people or communities. Indigenous values bring people together, across difference. Our land is also witness to the loss of indigenous values. The value of holding the land with care and reciprocity has been missing in mainstream society for far too long. The lack of indigenous worldviews in mainstream society is a society that lacks connection and respect for all, a society that values individualism rather than collectivism. Indigenous values express the importance of respecting the sovereignty of the land and her people: viewing the land as a sacred partner, rather than an object of possession and control. As a partner, the land and her people serve each other, providing nourishment collectively. The loss of indigenous voice and leadership across America has created a great imbalance. We have become a nation of people believing in invisibility and the retelling of history, a place where divisiveness is dominant and seeing truth is too painful. Although Indigenous people have paid the highest price, all others who share this land must understand the devastation will be and is being shared with each of us. A Framework: A Plan, a Path Forward Race, power, and privilege have a variety of meanings to each of us and elicit a diversity of emotional responses. In America, Indigenous people have lived experiences with this country like no other people sharing this land. Our collective lived experiences in America are vastly different, and these differences are important. Some experiences are a great reminder of the harsh realities of our history, and some a great reminder of how history comfortably instills hope and privilege in others. Americans and those who now live here share a society that places higher value on some lives over others. Today, we have a longstanding epidemic of missing and murdered Indigenous women and girls that is rarely reported on mainstream media or discussed in governmental or academic settings, while Indigenous women and girls go missing or murdered at rates higher than any other demographic. ?Native women are 2.5 times more likely to be sexually assaulted than any other demographic of women in the country,? I found a team of Native researchers headed by Crystal Echohawk. This team organized under the project ?Reclaiming Native Truth? released a report that revealed for the first time how the American public views Native Americans. The study found that the largest barrier to public sympathy for Native rights was ?the invisibility and erasure of Native Americans in all aspects of modern US society.?1 Not only is violence a common experience for Indigenous communities across the nation, access to the most basic human needs is also a struggle. There are Indigenous communities struggling today in 2022 for access to clean drinking water. Some tribal nations hold generations of their people exposed to dirty drinking water, with long-term exposure risks unknown.2 Many Americans live in places where boil water orders and water distribution centers are issued at first notice of a water quality concern, while there are Indigenous people and communities where water concerns have been ignored for decades. The challenges of and steps to address racism and racial inequities are complex to understand and to overcome. The Truth, Racial Health, and Transformation (TRHT) framework allows us to examine the entanglement of race/ism, healing, and meaningful relationship building. The TRHT is a comprehensive process to plan for and address the history and contemporary effects of racism. The TRHT framework centers its work on five key pillars: (1) Narrative Change, (2) Racial Healing and Relationship Building, (3) Separation, (4) Law, and (5) Economy.3 The framework helps to facilitate healing from a history often hidden, and a present day paralyzed with disconnection. Narrative Change and Racial Healing and Relationship Building are foundational pillars. These foundational pillars allow for sharing stories of both sorrow and strength, allowing for the truth to become visible and healing to happen. The Separation, Law, and Economy pillars address how America has historically sustained racial hierarchy and provides a path forward to disrupt structural and systemic racism.4 Collectively, the pillars of the TRHT framework support a process that ensures learning from the past and acknowledges the impact of the devastating mistakes made. Indigenous teachings and values of forgiveness, relationship building, and repair are important for all to consider. Rebuilding our relationships and connecting across difference can deepen the healing journey. These values bring us closer to healing. Recognizing the importance of each of the THRT framework pillars will make this healing even more profound. Deepening Our Connections, Our Relationships: Indigenous Understandings Today and for thousands of years, Indigenous people live(d) with reciprocity and gratitude for the land and community. Forced colonization and assimilation disrupted these ways of being and replaced them with unsustainable and harmful methods of living, attempting to erase indigenous systems with proven efficacy. These same systems innovatively customized to better fit our current evolving complex world. The attempted erasure of these systems is destructive for all people and the planet we share. Indigenous worldviews and values have worked, are working, and will work again, for not just Indigenous peoples, but also for all people. Through the creation of sacred spaces, we can strengthen relationships, understanding, and healing. By centering traditional knowledge and culture, we can relearn and implement those systems not always practiced but known. By centering indigenous culture and respect for the land, we can expand our understanding of the interconnectedness of all things, fostering greater empathy to shrink the vast divide in America. As former academician and author, Roman Krznaric describes in his book, Empathy Why it Matters, and How to Get it, empathy has the power to transform individuals and facilitate social and political change.5 The author further describes empathy as providing a revolution of human relationships: relationships and reciprocity, both core responsibilities for many Indigenous people. America and her people need an infusion of empathy and Indigenous people could be the teachers: teachers, whose wisdom we listen to and voices we amplify. Empathy allows for the divisiveness to soften and for the smiles to appear. It allows us to see the humanity of all people. Empathy is rooted within indigenous values, ceremonies, language, and all ways of being. Fundamental to indigenous culture is the care for all living things and the recognition of the interconnectedness and interdependency of each component of life. A belief held sacred is that we need each other, that each of us holds a piece to the advancement of the whole. This belief creates a sense of deep belonging, that each life matters and is needed.